A computational study of antireflection structures bio-mimicked from leaf surface morphologies. (June 2016) - Huang, Zhongjia; Shi, Tao; Zhang, Hui; Zhang, Meng; Huttula, Marko; Cao, Wei
Highlights: Biomimetic routes to design the antireflection gratings for solar cells. Micro and nano structural impacts on optical properties of the coatings. Numerical simulations of the biomimetic materials optics. Unification of antireflection property interpretations between artificial and natural light harvesting modules. Abstract: Conversions of solar energy can be realized artificially through photocells or naturally through foliage. In this article, we reported on designs of photocell antireflection (AR) patterns bio-mimicked from leaf surface morphologies. Numerical simulations of light transport were performed on photocell modules where the glass covers above the silicon slabs were patterned with two bionic structures of micro-hemispheres and pyramids. Backscattering of the light decreased considerably on the Si surface after introductions of the AR structures. The hemispheres possess better AR abilities than the pyramid counterparts when incident light shines at a tilted angle. Introducing nano structures on microspheres will further benefit the AR, with the nanorods lower more reflection rates than the nanodots gratings. Within the same morphology of nanorods decorated microspheres, the hemisphere of 3.0 μm diameter was found to have the best AR performances. Benefiting from the natural varieties of foliage surface structures, the present biomimetic route is hoped to serve as a start point for the AR cover designs in experimental realizations and theoretical predictions.